Jornalismo e humor : narrativas atrevidas na esquina - Bianca Magela Melo Silva (2011)
This work investigates the meeting between humor and narrative journalistic, through the observation of texts from the section esquina of the piauí magazine. Beginning from the unconventional journalism published in that section, we discussed the arrangements in the journalism production process, objectivity and rhetoric of self-legitimation in the news media. The humor brought questions to that activity, as its presence meant flexibleness to both text and the idea of truth. Interested in knowing the kind of narrative arranged by humor, we analysed the construction of the plot in fictional and non-fiction texts, trying to understand the path from where emerges the work and the sense. We followed thoughts that approach and keep away different narratives, showing how complex it is when talking about hard dichotomies. Support us in this reflection authors such as Paul Ricoeur, Wolfgang Iser and Thomas Pavel.